Kebijakan Publik Melalui Lensa Etnografi: Menggali Dinamika Sosial Melalui Kerangka Tahapan Kebijakan Michael Howlett - Lapasa, Amanca Pamalina; Azhar, Neng Zulfa (Universitas Airlangga, 2025)
This study explores social dynamics through an ethnographic approach through Michael Howlett's policy stage analysis framework. This study uses a qualitative method with a descriptive approach through secondary data collection from the internet and credible scientific journals. The ethnographic approach in policy studies uses policy ethnography as a framework for understanding Michael Howlett's policy stage analysis. This study provides insight into the meaning behind the social, cultural, and political contexts in the stages of public policy. The research findings show that the ethnographic approach through policy ethnography provides a social perspective at each stage of policy according to Michael Howlett's policy stage analysis framework. At the agenda-setting stage, policy ethnography uses an ethnographic approach as an initial step to map priority policy issues from direct observation of the community. At the policy formulation stage, policy ethnography identifies solutions to community needs related to problems faced from direct interactions that become policy formulation options. At the decision-making stage, policy ethnography decision-makers decide on policies to be implemented as a benchmark for desired goals through the social and cultural values of the community. At the policy implementation stage, policy ethnography conducts observations to understand the interaction between the policies being implemented and the responses of the targeted community. At the policy evaluation stage, policy ethnography evaluates the effectiveness of policies that have been implemented and assesses the impact of policies based on community perceptions and experiences. Policy ethnography refers to the social perspective at every stage of the policy. Keywords: Public policy, ethnographic approach, policy ethnography, social dynamics, policy stages